2002
DOI: 10.1159/000049425
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Endometriosis

Abstract: Various theories have been promulgated to explain the pathogenesis of endometriosis. Interest in the genesis of the endometriotic lesion has been a focus since the earliest investigations. More recently, investigators have addressed aspects of the immune system and local peritoneal factors that may be involved with both the histogenesis of endometriosis as well as its sequelae. This review will consider evidence for different theories of histogenesis and will discuss our current understanding of the contributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 81 publications
(94 reference statements)
0
33
0
1
Order By: Relevance
“…According to our and other previous studies, immune cells-derived cytokines, such as IL-1, may alone or in concert with estrogens, enhance the capability of ectopic endometrial cells to implant and develop into the host tissue, by inducing an angiogenic phenotype and stimulating the production of proinflammatory, growth, and tissue remodeling factors (Akoum et al 2000, 2002, Taylor et al 2002, Seli & Arici 2003, Wu & Ho 2003, Osteen et al 2004. Furthermore, our and other previous studies showed augmented sensitivity of endometriotic cells to the biological actions of IL-1 (Akoum et al 1995, 2002, Lebovic et al 2000, which may account for their ability to favor their own ectopic growth.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…According to our and other previous studies, immune cells-derived cytokines, such as IL-1, may alone or in concert with estrogens, enhance the capability of ectopic endometrial cells to implant and develop into the host tissue, by inducing an angiogenic phenotype and stimulating the production of proinflammatory, growth, and tissue remodeling factors (Akoum et al 2000, 2002, Taylor et al 2002, Seli & Arici 2003, Wu & Ho 2003, Osteen et al 2004. Furthermore, our and other previous studies showed augmented sensitivity of endometriotic cells to the biological actions of IL-1 (Akoum et al 1995, 2002, Lebovic et al 2000, which may account for their ability to favor their own ectopic growth.…”
Section: Discussionmentioning
confidence: 70%
“…Dual immuofluorescence analysis further identified endothelial cells and inflammatory cells, such as macrophages and T-lymphocytes, as cells markedly expressing IL-1RI in the stroma. These findings are suggestive of a relationship between IL-1RI expression and the implant's activity considering that active endometriotic lesions show a more marked vascularization and leukocyte infiltration (Halme et al 1987, Hill et al 1988, Wiegerinck et al 1993, Kokorine et al 1997, Jones et al 1998, McLaren 2000, Witz 2002, Taylor & Mueller 2004. …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Many theories have been proposed to explain this condition as the endometrium implantation theory, the coelomic metaplasia theory, the lymphatic and vascular metastasis theories, the mechanical transplant theory of remnant endometrium in spontaneous or operative delivery, the embryonic rests theory, a recent hypothesis based on the relationship of local immune factors [4].…”
Section: Discussionmentioning
confidence: 99%
“…Cependant l'association exceptionnelle d'une ascite à l'endomé-triose résulte de conditions très particulières favorables au développement des implants superficiels. Il s'agit d'anomalies cellulaires du liquide péritonéal (anomalies des macrophages avec diminution des cellules Natural Killer) et d'une sécrétion élevée de facteurs angiogéniques, de facteurs de croissance, d'adhésion, et des cytokines [8,9]. La physiopathologie de l'épanchement pleural reste également mal élu-cidée.…”
Section: Discussionunclassified